Negative effects of diabetes–related distress on health-related quality of life: an evaluation among the adult patients with type 2 diabetes mellitus in three primary healthcare clinics in Malaysia. Issue 1 (December 2015) - Chew, Boon-How; Mohd-Sidik, Sherina; Shariff-Ghazali, Sazlina
Abstract Background Patients with type 2 diabetes mellitus (T2D) often experienced change in life, altered self-esteem and increased feelings of uncertainty about the future that challenge their present existence and their perception of quality of life (QoL). There was a dearth of data on the association between diabetes-related distress (DRD) and health-related quality of life (HRQoL). This study examined the determinants of HRQoL, in particular the association between DRD and HRQoL by taking into account the socio-demographic-clinical variables, including depressive symptoms (DS) in adult patients with T2D. Methods This cross-sectional study was conducted in 2012–2013 in three public health clinics in Malaysia. The World Health Organization Quality of Life-Brief (WHOQOL-BREF), 17-items Diabetes Distress Scale (DDS-17), and 9-items Patient Health Questionnaire (PHQ-9) were used to measure HRQoL, DRD and DS, respectively. The aim of this research was to examine the association between the socio-demographic-clinical variables and HRQoL as well as each of the WHOQOL-BREF domain score using multivariable regression analyses. Results The response rate was 93.1 % (700/752). The mean (SD) for age was 56.9 (10.18). The majority of the patients were female (52.8 %), Malay (53.1 %) and married (79.1 %). About 60 % of the patients had good overall HRQoL. The mean (SD) for Overall QoL, Physical QoL, Psychological QoL, Social Relationship QoL and Environmental QoL were 61.7 (9.86), 56.7 (10.64), 57.9 (11.73), 66.8 (15.01) and 65.3 (13.02), respectively. The mean (SD) for the total DDS-17 score was 37.1 (15.98), with 19.6 % (136/694) had moderate distress. DDS-17 had a negative association with HRQoL but religiosity had a positive influence on HRQoL (B ranged between 3.07 and 4.76). Women, especially younger Malays, who had diabetes for a shorter period of time experienced better HRQoL. However, patients who were not married, had dyslipidaemia, higher levels of total cholesterol and higher PHQ-9 scores had lower HRQoL. Macrovascular complications showed the largest negative effect on the overall HRQoL (adjusted B = −4.98, 95 % CI −8.56 to −1.40). Conclusion The majority of primary care adult with T2D had good overall HRQoL. Furthermore, the independent determinants for HRQoL had also concurred with many past studies. In addition, the researchers found that DRD had negative effects on HRQoL, but religiosity had positive influence on HRQoL. Appropriate support such as primary care is needed for adult patients with T2D to improve their life and their HRQoL. Trial registration NMRR-12-1167-14158